Utilization of algal beach wracks as a supplementary substrate for enhancing mushroom production - Lavega, Rebeca; Rascón, Emilio; Soler-Rivas, Cristina; Pérez-Clavijo, Margarita (Frontiers in Marine Science, 2025)
Despite ecological protections, the Mar Menor lagoon in Spain continues to experience eutrophication, leading to uncontrolled proliferation of algae such as Caulerpa prolifera. When it decomposes, it reduces oxygen and creates sludge, causing fish and other aquatic animals to suffocate. Storms and seasonal changes then wash the uprooted algae ashore, generating foul odors and sludge buildup along the lagoon’s banks. In this study, the utilization of algal beach wracks as a component of substrates for mushroom cultivation was explored, assessing their potential to replace conventional lignocellulosic materials. Rinsed algal wracks were incorporated at 20%, 40%, and 60% (dry weight) into wheat straw-based substrates (patented formula no. 202430026), supplemented with 0%, 0.63%, 2.5%, or 5% additional nutrients, to cultivate four different mushroom species: oyster mushrooms (Pleurotus ostreatus), king oyster mushrooms (Pleurotus eryngii), Shimeji mushroom (Hypsizygus tessulatus), and Nameko mushroom (Pholiota nameko). Proximal analysis [moisture, pH, conductivity, nitrogen, organic load, and carbon/nitrogen (C/N) ratio], lignocellulosic content (lignin, cellulose, and hemicellulose), mushroom yield, and biological efficiency (BE) were analyzed and compared among formulations. Results demonstrated that utilizing 20% algal wracks significantly enhanced BE, with increases above 300% for H. tessulatus, 11% for P. ostreatus, and 9% for P. nameko, while P. eryngii showed similar yield and BE to the standard substrate (46.53% BE in the standard substrate compared to 48.37% in the algae-enriched substrate). These findings highlight the feasibility and environmental value of using algal beach residues as sustainable substrates for mushroom production, offering a circular bioeconomy alternative to current disposal practices in the Mar Menor region.